2015
DOI: 10.1038/ncomms7337
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for self-assembly of a cytolytic pore lined by protein and lipid

Abstract: Pore-forming toxins (PFT) are water-soluble proteins that possess the remarkable ability to self-assemble on the membrane of target cells, where they form pores causing cell damage. Here, we elucidate the mechanism of action of the haemolytic protein fragaceatoxin C (FraC), a α-barrel PFT, by determining the crystal structures of FraC at four different stages of the lytic mechanism, namely the water-soluble state, the monomeric lipid-bound form, an assembly intermediate and the fully assembled transmembrane po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
384
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 196 publications
(433 citation statements)
references
References 55 publications
(79 reference statements)
21
384
0
7
Order By: Relevance
“…The three-dimensional (3D) solution structures of four actinoporins have been solved: StI (García-Linares et al 2013), StII (Mancheno et al 2003), equinatoxin II (EqtII) from Actinia equina (Athanasiadis et al 2001;Hinds et al 2002) and fragaceatoxin C (FraC) from Actinia fragacea (Mechaly et al 2011;Tanaka et al 2015). The comparison of these structures in solution show a similar 3D fold formed by a central rigid and compact core consisting of two β sheets.…”
Section: Structure Of Sti and Stiimentioning
confidence: 99%
See 4 more Smart Citations
“…The three-dimensional (3D) solution structures of four actinoporins have been solved: StI (García-Linares et al 2013), StII (Mancheno et al 2003), equinatoxin II (EqtII) from Actinia equina (Athanasiadis et al 2001;Hinds et al 2002) and fragaceatoxin C (FraC) from Actinia fragacea (Mechaly et al 2011;Tanaka et al 2015). The comparison of these structures in solution show a similar 3D fold formed by a central rigid and compact core consisting of two β sheets.…”
Section: Structure Of Sti and Stiimentioning
confidence: 99%
“…These studies revealed the existence of multiple sites for lipid binding (Tanaka et al 2015); in fact two of these sites (L2 and L3) were considered to be initial binding sites similar to the POC binding site described for StII (Mancheno et al 2003), while L4 and L5 were hypothesized to be sites of low affinity for POC or perhaps highaffinity binding sites for lipids with headgroups other than POC (Tanaka et al 2015).…”
Section: Structure Of Sti and Stiimentioning
confidence: 99%
See 3 more Smart Citations